MicroRNA‐34c suppresses proliferation of vascular smooth muscle cell via modulating high mobility group box protein 1. Issue 7 (10th March 2020) - Chen, Li‐Bo; An, Zhe; Zheng, Hai‐Kuo; Wang, Xin‐Peng; Shan, Rui‐Ting; Mao, Cui‐Ying; Zhang, Wen‐Qi
Abstract: Background: Atherosclerosis is the most frequent pathological process that causes cardiovascular diseases. Objective: The present study aimed to confirm miRNAs associated with atherosclerosis and explore the molecular mechanism of miR‐34c and its target high mobility group box protein 1 (HMGB1) in the control of growth of smooth muscle cells in the development of atherosclerosis. Methods: Real‐time PCR was firstly performed to confirm miRNA correlation with atherosclerosis, and computational analysis and luciferase assay were performed to explore the target of miR‐34c, Western blot, and real‐time PCR were also utilized to reveal the effect of whether high glucose (HG) and miR‐34c affect miR‐34c, HMGB1 levels, NF‐κB p65 and TNF‐α levels, and the role of miR‐34c on vascular smooth muscle cells (VSMCs) viability induced by HG. Students' unpaired t test was performed to compare data between two groups. Results: MiR‐34c level was associated with atherosclerosis with different expression between VSMCs treated with high glucose or normal VSMCs. Then, HMGB1 is a virtual target of miR‐34c with predicted binding site resided in HMGB1 3′UTR and further verified by that miR‐34c remarkably reduced luciferase activity of wild HMGB1 3′UTR under a concentration‐dependent fashion, and miR‐34c cannot influence luciferase activity of mutant HMGB1 3′UTR. Conclusions: The results suggested miR‐34c might be a novel therapeutic strategy in the management of atherosclerosis by suppressing the expression of HGMB1 and its downstream effectors.